جهود إسماعيل الفاروقي في علم تاريخ الأديان - محمد خليفة حسن (International Institute of Islamic Thought, 2013)
يعرض البحث جهود إسماعيل الفاروقي في مجال تاريخ الأديان؛ وإسهامه في التأسيس المنهجي لهذا العلم على المستوى الدولي وعلى مستوى المنهج والمضمون. درس الفاروقي طبيعة التجربة الدينية في الإسلام، وعلاقتها بالتجارب الأخرى. وانخرط في الدرس الديني الحديث في الغرب، ومناهج فهم الدين ودراسته. وأبرز البحث دور الفاروقي في تطوير نظام من المبادئ الماوراء دينية؛ والمصدر الإلهي للأديان والحاجة إلى الدراسة النقدية للتراث الديني، أملاً في تعاون البشر في إقامة دين الفطرة، الذي يُوحِّد كل الأديان. This paper presents the efforts of Ismail al-Faruqi in the field of history of religions and his contributions in the methodological establishment of this field on the international level, particularly in the areas of methodology and content. Al-Faruqi studied the nature of the religious experience in Islam, and its relationship with other experiences.  He engaged in the modern religious studies in the West, and the methods of understanding and studying religion. The paper highlights Al-Faruqi's role in developing a system of Meta-Religious principles, the divine source of religions, and the need for critical assessment of religious heritage, in the hope that human beings would cooperate to establish the religion of Fitra (natural disposition), which unites all religions.